2007
DOI: 10.1007/s00259-007-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

The added value of [18F]fluoro-L-DOPA PET in the diagnosis of hyperinsulinism of infancy: a retrospective study involving 49 children

Abstract: These data demonstrate that PET with [(18)F]fluoro-L-DOPA is an accurate non-invasive technique allowing differential diagnosis between focal and diffuse forms of HI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
47
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 38 publications
4
47
0
5
Order By: Relevance
“…In this field, the lack of a prompt availability of 18 F-DOPA may be overcome by using radiolabelled somatostatin analogues. The study confirmed, in a relatively high number of patients, the well-known [9,14] high sensitivity, specificity, positive and negative predictive value (100%) of 18 F-DOPA PET/CT in detecting the focal form of CHI. Furthermore, the high accuracy of 18 F-DOPA PET/CT, confirmed by histopathology in the majority of the cases, was also achieved by combining functional PET information with the anatomical information provided by ceCT.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…In this field, the lack of a prompt availability of 18 F-DOPA may be overcome by using radiolabelled somatostatin analogues. The study confirmed, in a relatively high number of patients, the well-known [9,14] high sensitivity, specificity, positive and negative predictive value (100%) of 18 F-DOPA PET/CT in detecting the focal form of CHI. Furthermore, the high accuracy of 18 F-DOPA PET/CT, confirmed by histopathology in the majority of the cases, was also achieved by combining functional PET information with the anatomical information provided by ceCT.…”
supporting
confidence: 61%
“…This approach may reduce the possibility of treatment-related events as diabetes or exocrine pancreas deficiency [8]. 18 F-DOPA is a precursor of catecholamine and is taken up by the neuroendocrine cells by the pancreatic islet by using the large aminoacid transporter 2 [9]. Pancreatic neuroendocrine cells are able to take up amino acids and to transform them into biogenic amine by means of decarboxylation.…”
mentioning
confidence: 99%
“…Konwencjonalne badania, takie jak ultrasonografia, tomografia komputerowa lub rezonans magnetyczny, nie są w stanie wykryć zmian ogniskowych w trzustce [4][5][6][7][8].Obrazowanie przy pomocy badania PET (ang. Positron Emission Tomography) ze znacznikiem [18F]-L-3,4-dihydroksyfenyloalaniny (18-F-DOPA) zrewolucjonizowało diagnostykę wrodzonego hiperinsulinizmu.…”
Section: Wstępunclassified
“…The authors concluded by proposing 18 F-DOPA-PET/CT as the best modality of choice in locating a focal lesion [36] . Riberio et al [40] did a retrospective study in 2007 on forty nine children with CHI who had undergone 18 F-DOPA-PET/CT scanning. They identified abnormal focal pancreatic uptake of 18 F-DOPA in 15 children, where diffuse radio-tracer uptake was observed in the pancreatic area in the other 34 children.…”
mentioning
confidence: 99%
“…In children who underwent both PET and PVS, the results were concordant in 11 out of 12. The authors concluded that PET scan with 18 F-DOPA is an accurate non-invasive technique allowing differential diagnosis between focal and diffuse forms of CHI [40] . Arbizu Lostao et al [41] reported their first patient from Spain in whom the diagnosis of focal CHI was made in a 13 month old child using combined genetic analysis [paternal heterozygous mutation (G111R) in the ABCC8 gene] and 18 F-DOPA-PET/CT imaging (focal uptake in the body of the pancreas) was successfully treated by surgery.…”
mentioning
confidence: 99%